2019
DOI: 10.1038/s41586-019-1644-y
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota regulate neuronal function and fear extinction learning

Abstract: Multicellular organisms have co-evolved with complex consortia of viruses, bacteria, fungi and parasites, collectively referred to as the microbiota. In mammals, changes in the composition of the microbiota can influence a wide range of physiologic processes (including development, metabolism, and immune cell function) and are associated with susceptibility to multiple diseases. Alterations in the microbiota can also modulate host behaviors such as social activity, stress, and anxiety-related responses that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
245
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(275 citation statements)
references
References 78 publications
7
245
2
4
Order By: Relevance
“…In that line of ideas, it was demonstrated that exposure to microbiota during the neonatal period restores fear extinction learning in adulthood. 86…”
Section: Imprinting Of Microbiotamentioning
confidence: 99%
“…In that line of ideas, it was demonstrated that exposure to microbiota during the neonatal period restores fear extinction learning in adulthood. 86…”
Section: Imprinting Of Microbiotamentioning
confidence: 99%
“…Within the complex interplay between the gut microbiome and the CNS, a role for brain barriers and neuroinflammation is becoming important (Braniste et al, 2014;Cerovic et al, 2019;Parker et al, 2019;Wang et al, 2019). The impact of the gut microbiome composition on CNS health was reported (Amedei and Boem, 2018;Chu et al, 2019;Sherwin et al, 2019;Virtue et al, 2019). Recent work demonstrated that GM composition controls BBB development and permeability in mice (Braniste et al, 2014).…”
Section: The Gut-brain Axis and Neurodegeneration: Is There A Barriermentioning
confidence: 99%
“…A growing body of evidence shows that the resident bacteria in the gastrointestinal tract, collectively the gut microbiome, play a role in normal brain function and behavior, and may have relevance for neurodevelopmental disorders. Disruptions of the gut microbiome lead to alterations in gene expression and epigenetic regulation in the brain as well as alterations in neuronal activity patterns and synaptic plasticity in multiple limbic substructures [6][7][8] . Studies examining the composition of the microbiome in patients with ASD have repeatedly found that patients have differences in microbiome composition [9][10][11] , but specific microbial changes associated with a diagnosis have varied between studies.…”
Section: Introductionmentioning
confidence: 99%
“…mice that are raised completely sterile with no internal or external microbiome) have marked deficits in social behaviors and in gene expression profiles in multiple brain regions related to regulation of these behaviors [12][13][14] . Additionally, mice who have had their microbiomes depleted with antibiotics show deficits in social behavior, cognitive flexibility, and multiple other ASD-like behaviors 6,15,16 . At a cellular and molecular level, disruption of the microbiome with prolonged antibiotics leads to changes in neuronal and glial structure, changes in cell firing patterns, and altered transcriptional and epigenetic signatures in multiple brain structures 6,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%